The emergence of a texas collaboration to improve well-being in learning health systems. Issue 1 (1st January 2021) - Harris, Toi B.; Nanda, Anil; Sargsyan, Lilit A.; Chen, Wei-Jung A.; Christner, Jennifer G.
ABSTRACT: Prior models of well-being have focused on resolving issues at different levels within a single institution. Changes over time in medicine have resulted in massive turnover and reduced clinical hours that portray a deficit-oriented system. As developments to improve purpose and professional satisfaction emerge, the Texas Medical Association Committee on Physician Health and Wellness (PHW) is committed to providing the vehicle for a statewide collaboration and illuminating the path forward. To describe the existing health and wellness resources in Texas academic medical centers and understand the gaps in resources and strategies for addressing the health and wellness needs in the medical workforce, and in student and trainee populations. Various methods were utilized to gather information regarding health and wellness resources at Texas academic medical centers. A survey was administered to guide a Think Tank discussion during a PHW Exchange, and to assess resources at Texas academic medical centers. Institutional representatives from all Texas learning health systems were eligible to participate in a poster session to share promising practices regarding health and wellness resources, tools, and strategies. Survey responses indicated a need for enhancing wellness program components such as scheduled activities promoting health and wellness, peer support networks, and health and wellness facilities in academic medical centers. Answers collected during the Think Tank discussion identified steps needed to cultivate a culture of wellness and strategies to improve and encourage wellness. The Texas Medical Association Committee on Physician Health and Wellness and PHW Exchange provided a forum to share best practices and identify gaps therein, and has served as a nidus for the formation of a statewide collaboration for which institutional leaders of academic medical centers have affirmed the need to achieve the best result.